Water scarcity: A global hindrance to sustainable development and agricultural production – A critical review of the impacts and adaptation strategies - Auindrila Biswas; Sourakanti Sarkar; Sumanta Das; Suman Dutta; Malini Roy Choudhury; Anmol Giri; Bimal Bera; Koushik Bag; Bishal Mukherjee; Koushik Banerjee; Debaditya Gupta; Debasish Paul (Cambridge Prisms: Water)
Water is essential for sustaining life and required for carrying out basic daily activities. Even though water covers the vast majority of the earth’s surface, the availability of fresh water, which is necessary to maintain human activities, is limited, making it a scarce resource. Climate change, overexploitation of groundwater, and population growth are all putting significant pressure on natural water sources, which pose a serious threat to various sectors of society, especially in agriculture. Future projections of freshwater availability indicate agriculture production will suffer a significant shock globally, including in India, leading to a threat to food security and sustainability. To ensure the sustainability of this vital resource, it is crucial to use water sensibly. Moreover, it is essential to adopt certain strategies to manage agricultural water use effectively. This includes adopting various water-efficient techniques such as ‘micro-irrigation’, ‘irrigation scheduling’, ‘conservation agriculture’, ‘crop switching’ and so on. In this review, firstly, we discuss water scarcity and its types, causes, crisis for water shortages and hindrance to sustainable development from a global perspective emphasizing the Indian scenario as a developing nation. Secondly, we elaborated our discussion on water scarcity in agriculture including the impacts of water scarcity on agricultural production and its connection to climate change, population growth, and overexploitation of natural resources globally focusing on the Indian scenario. In addition, innovative water management practices and adaptation strategies to manage agricultural water use, constraints, and the need for further research are also covered. It is anticipated that this review will benefit researchers and policymakers by providing useful information on the impacts of water limitation and adoption strategies.